The Santri's Movement of Sharing Enthusiasts in Forming a Social Care Character - Aritonang, Asmidar Efendi; Daulai, Afrahul Fadhila (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The aim of the research is to describe the activities of the Santri movement, which likes to share in forming socially caring characters at the Tahfizh Azhar Islamic Boarding School in the North Labuhanbatu Center, which is located at Sukan Mulia Hamlet, Damuli Pekan Village, Kualuh Selatan District, North Labuhanbatu Regency. This research is qualitative with a case study approach. Sources of research data were obtained from school principals, GSGB activity supervisors, and students. The data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation, and verification or drawing conclusions, The results showed that the background for the formation of these activities was to foster a socially caring attitude as a provision for living a social life in society. Facilities, good cooperation, and the role of parenting are the supporting factors in this activity, and the inhibiting factors are the awareness of the students and the implementation schedule, which is not yet fixed. In terms of its implementation, this activity has been going well, as can be seen from the achievement of its objectives, namely, to create students with socially caring characters.